Quality analysis and function prediction of soil microbial communities of Polygonatum cyrtonema in two indigenous-origins - Yang, Li; Yang, Qing; Wulu, Jiansang; Wang, Yue; Jin, Wenfang; Yan, Zhigang; Zhang, Zhifeng (Frontiers in Microbiology, 2024)
analysis between the microbiota and the chemical content from 12 different collecting spots was performed by GraphPad Prism. Burkholderia-Caballeronia-Paraburkholderia, Acidibacter, and Amycolatopsis show an inverse proportionality to total polysaccharides and saponins, while Enterobacter shows a direct proportionality to total polysaccharides and inverse proportionality to saponins. The metabolism pathways show a significant positive correlation with PCH polysaccharides and saponins. This study provide new insights into the mechanisms underlying the quality differences between the two major indigenous areas.